Fareha by CikFa / Mira Izzatie Rahim - Rahim, Mira Izzatie (2021)
Fareha by CikFa is a hijab that is well-known in Malaysia today with it’s concept Anti-Kedut also known as Ironless. It because one of the top trending in Malaysia ever since hijab in Bawal Style getting more request. Cik Fa a successful business women release her new unique and stunning design of hijab with variety of pattern to get. It is now available to get anywhere in each state.